The experience as a creative process in visual art classes (Revista Apotheke, 2022)
This article emphasizes the importance of experience during the artistic creative process for visual works. Presents the creative process of students from the 7th grade of elementary school in a high school in Sao Bernardo do Campo, São Paulo,during art classes in 2015.
Keywords: Exeprience; Creativity; Color; Composition; processs